Quality-Oriented Preventive Maintenance Practices and Performance among Malaysian SMEs Manufacturing Organizations: Findings from a Survey - Halim Mad Lazim; Che Azlan Taib; Hendrik Lamsali; Mohamed Najib Salleh; Chandrakantan Subramaniam (International Journal of Supply Chain Management, 2017)
Maintenance has become an important aspect in the manufacturing environment. There are a number of new technology and advancement in the manufacturing industry which can improve daily operations and production. In order to ensure smooth daily operations, the aspect of maintenance must be given a priority. A quality-oriented preventive maintenance practices such as preventive maintenance team, preventive maintenance strategy and planned maintenance can help to avoid any potential stoppages and disruptions of equipment from occurring in their daily operations. Preventive maintenance (PM), utilises total employee involvement in the maintenance activities. Operators and all employees should be actively involved in a maintenance programme that enable to avoid any disruptions, breakdowns, stoppages, failures, and so forth in order to improve manufacturing performance. Therefore, in the highly competitive manufacturing industries, the ability and reliability of equipment that well-maintained is very important in order to achieve desired performance. Furthermore, several studies in the literature argue that further research is required in the area of maintenance and operations management. This study investigates the extent of PM practices in the Malaysian Small and Medium Enterprises manufacturing organizations and to investigate the relationship between PM practices and performance. The hypotheses were analysed using Smart PLS and some important findings were discussed. The results imply that PM practices significantly improved manufacturing performance. For instance, PM strategy was positively and significantly related to financial, innovation and organizational capabilities. However, there were few research insignificant findings found for example planned maintenance is insignificant with innovation. Furthermore, the contributions and limitations of the study also discussed accordingly